1994
DOI: 10.1111/j.1365-3083.1994.tb03442.x
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Synovial Tissue‐Derived Human Monoclonal Immunoglobulin M Rheumatoid Factor to Immunoglobulin G Preparations of Differing Galactose Content

Abstract: There are several sites on IgG Fc that have been reported to be the epitopes for binding rheumatoid factors (RF). It is now established that there are alterations in the oligosaccharides on IgG from patients with rheumatoid arthritis and it has been suggested that these changes may enhance immune complex and cryoglobulin formation. We have used a series of IgG preparations differing in their content of oligosaccharide chains lacking galactose from 18 to 86% to determine whether changes in sugar content affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…Three antibodies exhibited specifi city to a single domain: both RFAbs TS2 and TS1 to a region in the CH3 domain, epitope (iii) 360-KNQVSLTCLVKGFYP-374 and RFAb SJ1 to a region in the CH2 domain, epitope (ii) 294-EQYNSTYRVVSVLTV-308. Overall, this data was consistent with the monospecifi city of the rheumatoid factors [12]. Interestingly epitope (iii) was adjacent to amino acids previously cited RF antigenic sites but novel in terms of its position (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Three antibodies exhibited specifi city to a single domain: both RFAbs TS2 and TS1 to a region in the CH3 domain, epitope (iii) 360-KNQVSLTCLVKGFYP-374 and RFAb SJ1 to a region in the CH2 domain, epitope (ii) 294-EQYNSTYRVVSVLTV-308. Overall, this data was consistent with the monospecifi city of the rheumatoid factors [12]. Interestingly epitope (iii) was adjacent to amino acids previously cited RF antigenic sites but novel in terms of its position (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Details of the characterisation and purifi cation of these antibodies TS2, TS1, SJ1, PRSJ2 and PRTS1 has previously been reported [12]. In particular RFAbs TS2, TS1 and SJ1 were monospecifi c with regard to their reactivity against native IgG, whilst RFAbs PRSJ2 and PRTS1 were polyspecifi c.…”
Section: Rheumatoid Factor Antibodiesmentioning
confidence: 99%
“…It has also been shown that, in vitro, terminal GlcNAc on IgG is accessible for binding with mannosebinding protein and this, in turn, results in activation of complement (17). In addition, rheumatoid factors may selectively bind IgG that is hypogalactosylated (18), which may explain why immune complexes are abundant in RA. There may be factors other than disease that influence the oligosaccharide composition of IgG, since a greater degree of hypogalactosylation occurs at the extremes of life in healthy individuals (19).…”
mentioning
confidence: 99%
“…IgG1, the dominant ACPA isotype, is recognized by all of the so far described RA-derived RF (29). Moreover, RF seem to exhibit enhanced avidity toward agalactosylated forms of IgG (30), which are elevated in RA patients with high disease activity (31). In RA patients, it was reported that ACPA IgG1 tended to be more agalactosylated compared with total serum IgG1, and that, in the joints, ACPA IgG1 was more heavily agalactosylated than in the general circulation (32).…”
mentioning
confidence: 99%